2014
DOI: 10.1007/s10689-014-9742-3
|View full text |Cite
|
Sign up to set email alerts
|

The secondary bile acid, deoxycholate accelerates intestinal adenoma–adenocarcinoma sequence in Apc min/+ mice through enhancing Wnt signaling

Abstract: Colorectal cancer is one of the leading causes of cancer deaths. It correlates to a high fat diet, which causes an increase of the secondary bile acids including deoxycholate (DOC) in the intestine. We aimed to determine the effects of DOC on intestinal carcinogenesis in Apc (min/+) mice, a model of spontaneous intestinal adenomas. Four-week old Apc (min/+) mice were treated with 0.2 % DOC in drinking water for 12 weeks. The number and size of tumors were measured, and tissue sections were prepared for the eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…While BAs have been shown to interact with the EGFR pathway in numerous tissues, including the colon (10,44), liver (63), bile ducts (74,75), stomach (73), and esophagus (3), discrepancies in the literature exist here as well. For example, in Caco-2 cells, DCA was found to inhibit barrier function via EGFR phosphorylation (62), although EGF administration is typically associated with improved barrier function (6, 7).…”
Section: Discussionmentioning
confidence: 89%
“…While BAs have been shown to interact with the EGFR pathway in numerous tissues, including the colon (10,44), liver (63), bile ducts (74,75), stomach (73), and esophagus (3), discrepancies in the literature exist here as well. For example, in Caco-2 cells, DCA was found to inhibit barrier function via EGFR phosphorylation (62), although EGF administration is typically associated with improved barrier function (6, 7).…”
Section: Discussionmentioning
confidence: 89%
“…In this chapter, we will describe techniques for studying colon cancer development in Apc min/+ mice on a C57BL/6J (B6) genetic background, focusing on Dextran Sulfate Sodium-induced (DSS) [1417], high fat diet-induced [1820], and bile acid supplementation [21, 22] as environmentally modifiable models of colorectal cancer. This chapter also includes protocols describing extraction and purification of DSS-contaminated RNA [23], as well as sampling, harvesting, and tissue processing.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal tumors were categorized as small (<1 mm), medium (1‐2 mm), or large (>2 mm). Swiss rolled distal small intestine and colon tissues were fixed in 10% buffered formalin . The tissue sections were used for hematoxylin and eosin (H&E) staining and immunohistochemical (IHC) staining.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple intestinal neoplasia ( Apc min/+ ) mice spontaneously develop multiple tumors in the intestine and are an established model for studying intestinal carcinogenesis. In our previous work, we aimed to determine the effects of DCA on intestinal carcinogenesis in Apc min/+ mice and found that DCA accelerates the intestinal adenoma‐adenocarcinoma sequence . Next, we investigated the effect of DCA on the induction of intestinal dysbiosis and its roles in intestinal carcinogenesis and demonstrated that DCA‐induced changes to the microbial community promoted intestinal carcinogenesis .…”
Section: Introductionmentioning
confidence: 99%